Lean combustion : technology and control - Dunn-Rankin, Derek; Therkelsen, Peter (Academic Press is an imprint of Elsevier, 2016)
Lean Combustion: Technology and Control, Second Edition outlines and explains the latest advances in lean combustion technology and systems. Combustion under sufficiently fuel-lean conditions can have the desirable attributes of high efficiency and low emissions. The book offers readers both the fundamentals and latest developments in how lean burn (broadly defined) can increase fuel economy and decrease emissions, while still achieving desired power output and performance. This volume brings together research and design of lean combustion systems across the technology spectrum in order to explore the state-of-the-art in lean combustion. Readers will learn about advances in the understanding of ultra-lean fuel mixtures and how new types of burners and approaches to managing heat flow can reduce problems often found with lean combustion (such as slow, difficult ignition and frequent flame extinction). This book offers abundant references and examples of real-world applications. New to this edition are significantly revised chapters on IC engines and stability/oscillations, and new case studies and examples. Written by a team of experts, this contributed reference book aims to teach its reader to maximize efficiency and minimize both economic and environmental costs. Presents a comprehensive collection of lean burn technology across potential applications, allowing readers to compare and contrast similarities and differencesProvides an extensive update on IC engines including compression ignition (diesel), spark ignition, and homogeneous charge compression ignition (HCCI)Includes an extensive revision to the Stability/Oscillations chapterIncludes use of alternative fuels such as biogas and hydrogen for relevant technologiesCovers new developments in lean combustion using high levels of pre-heat and heat recirculating burners, as well as the active control of lean combustion instabilities